The role of preferences, attitudes, and personality traits in labor market matching - Michael Haylock; Patrick Kampkötter (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
We provide new evidence of worker-firm matching based on preferences, attitudes and personality traits using new, representative matched employer-employee data from Germany. Time-constant firm characteristics explain a significant proportion of total variance in a series of outcome variables commonly applied in behavioral economics research. Hence, behavioral characteristics play an important, yet under researched, role in the labor market matching process.
urn:nbn:de:bsz:21-dspace-934270
Keywords: D90; D91; J01; M50; 330; Preferences; Attitudes; Personality; Sorting; Matching